2013
DOI: 10.1308/003588413x13629960049117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of novel vitamin D receptor activator paricalcitol on renal ischaemia/reperfusion injury in rats

Abstract: Paricalcitol therapy improved renal I/R injury in terms of serum and histopathological parameters. These potential beneficial effects need to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Quite few of them have explored the effect of VDR in clinical AKI or in vivo models. Azak A et al has reported that VDR activator paricalcitol could mitigate renal ischemia/reperfusion injury in rats 22 . Our quite recent work also showed a promising protection of vitamin D-VDR signaling against apoptosis in an AKI model induced by LPS 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Quite few of them have explored the effect of VDR in clinical AKI or in vivo models. Azak A et al has reported that VDR activator paricalcitol could mitigate renal ischemia/reperfusion injury in rats 22 . Our quite recent work also showed a promising protection of vitamin D-VDR signaling against apoptosis in an AKI model induced by LPS 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond their role in maintaining calcium and phosphate homeostasis, vitamin D metabolites influence the expression of more than 200 target genes, 19 including genes that affect a variety of critical immunomodulatory pathways relevant to AKI. 125,126 In animal models, pre-administration of 1,25D attenuated AKI resulting from a variety of nephrotoxic insults, including ischemia-reperfusion injury, [127][128][129] gentamicin, 130 cyclosporine, 131 cisplatin, 132 glomerulonephritis, 133 and obstruction. 134 Furthermore, de Braganca et al 135 investigated the effects of dietary-induced 25D deficiency on the severity of AKI in rats.…”
Section: Vitamin D Metabolites As Novel Therapies In Aki and Criticalmentioning
confidence: 99%
“…assessed the relationship between serum vitamin D levels and the prognosis of AKI and showed that the degree of 1,25 (OH) 2 D 3 deficiency is associated with the severity of AKI [ 74 ]. Ischemia/reperfusion (IR) is an important pathogenic factor for AKI, and it has been shown that therapy with the VDR activator paricalcitol can attenuate renal IR injury by improving tubular necrosis and medullar congestion [ 75 ]. Furthermore, Gonçalves et al .…”
Section: Vdr In Secondary Kidney Diseasesmentioning
confidence: 99%